Effects of Dietary Levels of Calcium and Nonphytate Phosphorus in Broiler Starter Diets on Total and Water-Soluble Phosphorus Excretion as Influenced by Phytase and Addition of 25-Hydroxycholecalciferol - Coto, C.A.; Yan, F.; Cerrate, S.; Wang, Z.; Sacakli, P.; Waldroup, P.W. (International Journal of Poultry Science, 2007)
A study was conducted utilizing a 2 x 2 x 4 x 4 factorial arrangements in which a nutritionally adequate diet was fed with and without 1200 FTU/kg of phytase and with or without 69 μg/kg of 25-hydroxycholecalciferol, four levels of nonphytate phosphorus (NPP) (0.35, 0.40, 0.45, and 0.50%) and four levels of calcium (2:1 Ca:NPP ratio, 0.2% Ca less than the 2:1 ratio, 0.2% Ca more than the 2:1 ratio, and 0.4% Ca more than the 2:1 ratio) for a total of 64 treatments, each fed to two replicate pens of five male broilers in wire-floored battery brooders. At 14 d of age excreta samples were collected, frozen, freeze dried, and analyzed for total P (TP), Ca, and water-soluble P (WSP). The ratio of WSP/TP was calculated from these data. The TP, Ca and WSP in excreta increased as the NPP content of the diet increased. Phytase supplementation reduced TP and Ca but increased WSP concentration and the WSP/TP ratio; this effect might be reversed if levels of NPP lower than those evaluated in the present study are utilized to account for the improvement on phytate phosphorus digestion. The addition of Hy-D reduced TP and Ca concentration in broiler excreta. The most remarkable effect was seen by increasing dietary calcium levels above the 2:1 Ca:NPP ratio typically used in the poultry industry. As the dietary Ca increased, there were significantly reduced excreta levels of TP, WSP and the WSP/TP ratio was significantly reduced. Compared to chicks fed diets with the 2:1 Ca:NPP ratio, the WSP in excreta was reduced 40% by adding 0.20% more Ca and 54% by adding 0.40% more Ca. As the WSP fraction of broiler litter is the primary concern in eutrophication, increasing the dietary Ca level in conjunction with feeding closer to the P requirement should be a cost-effective means of combating the adverse effects of broiler litter on pastures.